Dry mechanical-electrochemical polishing of selective laser melted 316L stainless steel. (August 2020) - Bai, Yuchao; Zhao, Cuiling; Yang, Jin; Fuh, Jerry Ying Hsi; Lu, Wen Feng; Weng, Can; Wang, Hao
Abstract: This paper aims to improve the surface quality of 316L stainless steel parts manufactured by selective laser melting (SLM) using dry mechanical-electrochemical polishing (DMECP). DMECP is an advanced surface finishing method combining the advantages of both mechanical and electrochemical polishing techniques in a more environmentally friendly manner. In this paper, the SLM process-related defects causing poor surface quality are analysed first. The material removal mechanism of DMECP is investigated to continuously remove the oxide layers formed during polishing. Surface morphology and roughness evolution under different polishing conditions are characterised. The top surface roughness can be reduced by over 91% from 8.72 μm to 0.75 μm compared to side surface by over 93% from 12.10 to 0.80 μm. The material removal on the top surface is more efficient than that on the side surface under the same polishing condition. The secondary defects formed during polishing can be removed using mechanical polishing mode. The chemical element composition of the polished surface exhibits almost identical content to the initial 316L powders. Compared with the initial dark and rough surfaces, the results validate the capability of DMECP as an effective tool to improve the SLM surface quality and achieve a mirror finish. Graphical abstract: Unlabelled Image Highlights: Dry mechanical-electrochemical polishing (DMECP) is applied to finish selective laser melted (SLMed) surfaces. The submicron-level surface roughness is achieved on SLMed metal parts. Defects on SLMed 316L stainless steel are analysed and removed. The relationship between polishing parameters and surface quality is established. The material removal cycle and mechanism of DMECP are elucidated.